Syrian refugees under temporary protection and the YEDAM Service Network in Türkiye: An ecological perspective on regional balance - Vuraloğlu, Emre (Addicta: The Turkish Journal on Addictions, 2026)
This study aimed to examine, at an ecological level, the relationship between the regional distribution of Syrian refugees under temporary protection across Türkiye and the numerical distribution of Green Crescent Counseling Centers (YEDAM). This descriptive and cross-sectional study was conducted using publicly accessible data from the Presidency of Migration Management of the Republic of Türkiye Ministry of Interior and YEDAM, obtained in October 2025. For each province and region, the number of registered Syrians under temporary protection, the ratio of registered Syrians to the total provincial population, and the number of YEDAM centers constituted the study variables. The Kruskal–Wallis H test, Bonferroni-corrected Dunn multiple comparison test, and Spearman correlation analysis were applied for statistical analyses. A statistically significant positive correlation was found between the number of registered Syrians and the number of YEDAM centers nationwide (p = 0.015). The number of Syrians per YEDAM center was significantly higher in the Mediterranean and Southeastern Anatolia regions compared with the Black Sea and Eastern Anatolia regions (p < 0.01). The findings indicate that YEDAM has established a strong foundation with its nationwide service network; however, increasing the number of centers in regions with high immigrant density could further enhance equity in service provision.